Hova lettek az orvosok? Az orvosok külföldre vándorlása és pályaelhagyása Magyarországon 2003-2011 - Júlia Varga (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2015)
– This paper employs large-scale individual-level panel data-set to determine the changes in the probability of migration and attrition of Hungarian doctors between 2003 and 2011. The study uses event history modelling, competing risk models. The results show that first after the EU accession, then after the spring of 2010, and finally after the relaxation of the Austrian and German temporary employment limits, the hazard of doctors' migration increased. Results also show that in Hungary, in addition to migration, doctors' attrition is also a severe problem. Exits from physicians' and dentists' pool by migration, going to another job in Hungary and by going to inactivity are about equally likely.
Keywords: C41; C55; I10; J4; J40; J45; J60; J61; 330; Doctors' migration; doctors' attrition; competing risk modell